Avaliação de funcionamento das bombas hidráulicas do sistema de tratamento de efluentes da Empresa Parker Hannifin - Haibara, Jody Baglioni [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
On the field of the projects of hydraulic systems exists a lot of worries when we talk about the calculate of hydraulic pumps. In this case some facts must be considerate: length of tubes, fluid characteristics, height gauge, temperature, pressure, characteristics of tubes, flow required and others. For that mathematic calculates must be developed with the objective to optimize hydraulic pumps and agree to find an ideal machine (that don't requires more energy than necessary or less energy than it requires; that is the more critical case, cause exists the risk that the fluid pumped do not agree to become in your destiny). The wrong calculate of this machine can super-size its, bringing an excessive energy consumption. Actually it's an important subject because we are in the age of lack of energy what turn it more expensive. So the correct sizing of a hydraulic pump is connected with the fact that you have to uses the enough energy resources avoiding waste. The calculate of ideal pump in the pumping system is studied during years and a lot of specialists in this subject develop equations and theories to calculate its. Some researches study about this subject and all of them become to the same conclusion: to find the ideal pump we have to know the characteristics of fluid (cinematic viscosity), the required flow , overall yield (overall of motor x overall of pump) the high gauge or discharge pressure and the loss of repression. The pressure drop can be calculated with different theories: using Hazen-Williams, Darcy e Weisbach or Chézy (1775 - that starts the researches to calculate the pressure drop). Although the most used theory and what is most near to reality is the Darcy's equation. So, in this job the Darcy's equation were choice to calculate the drop pressure that consider what kind of flow we are studying: laminar or turbulent. The determination of the best pump to be used in the ... ( complete abstract click eletronic access below)

No campo dos projetos de sistemas hidráulicos existe uma série de preocupações quando tratamos do dimensionamento de bombas hidráulicas. Neste caso uma série de fatores devem ser levados em consideração: comprimento da tubulação, características do fluido, altura manométrica, temperatura, pressão, características da tubulação, vazão requerida entre outros. Para tanto são necessários cálculos matemáticos que visam otimizar as bombas hidráulicas e encontrar uma máquina ideal (que não utilize mais energia do que necessário ou menos energia do que lhe é requerido; sendo este o caso mais crítico, na qual corre-se o risco de o fluido bombeado não conseguir, sequer, chegar ao seu destino). O cálculo exagerado desta máquina pode superdimensioná-la causando um consumo de energia. Assunto este de grande relevância pois estamos na era da falta de energia o que a torna mais cara. Sendo assim o dimensionamento correto de uma bomba hidráulica corresponde à utilização correta dos recursos energéticos evitando desperdícios. O cálculo da bomba ideal em um sistema de bombeamento é estudado a anos e uma série de especialistas no assunto desenvolveram fórmulas e teorias. Apesar de diversos pesquisadores terem estudado o assunto todos chegaram à mesma conclusão: para encontrar a bomba ideal devemos saber a viscosidade do fluido, vazão requerida, rendimento global do motor x rendimento da bomba e altura manométrica. A perda de carga da tubulação deve ser tratada de forma diferenciada pois várias são as formas de calculá-la. Podemos lançar mão da fórmula de Hazen-Williams, Darcy e Weisbach de Chézy (1775) que iniciou as pesquisas para o cálculo desta perda. No entanto a fórmula adotada atualmente como a mais próxima da realidade é a de Darcy. Foi escolhido para este trabalho a fórmula da perda de carga de Darcy que leva em consideração o tipo de escoamento ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Bombas hidraulicas eletricas; Tubulação - Dinamica dos fluidos; Maquinas hidraulicas - Consumo de energia; Bombas centrifugas; Hydraulic machinery